Bibliometric and visualized analysis of global research on microRNAs in gastric cancer: from 2013 to 2023 - Wang, Xiaoqin; Wang, Caihua; Han, Wenjin; Ma, Congmin; Sun, Jiaru; Wang, Tianmeng; Hui, Zhaozhao; Lei, Shuangyan; Wang, Ronghua (Frontiers in Oncology, 2024)
Gastric cancer (GC) imposes a heavy burden on global public health, and microRNAs (miRNAs) play a crucial role in the diagnosis and treatment of GC. Therefore, it is necessary to clarify the hotspots and frontiers in the field of miRNAs in GC to guide future research. A total of 2,051 publications related to miRNAs in GC from January 2013 to December 2023 were searched from the Web of Science Core Collection database. CiteSpace was used to identify research hotspots and delineate developmental trends. In the past decade, China, Nanjing Medical University, and Ba Yi were the most contributing research country, institute, and author in this field, respectively. The role of miRNAs as biomarkers in GC, the mechanism of miRNAs in the progression of GC, and the impact of the mutual effects between miRNAs and Helicobacter pylori on GC have been regarded as the research hotspots. The mechanisms of miRNAs on glucose metabolism and the application of the roles of circular RNAs as miRNA sponges in GC treatment will likely be frontiers. Overall, this study called for strengthened cooperation to identify targets and therapeutic regimes for local specificity and high-risk GC types, and to promote the translation of research results into clinical practice.